THE OCCURENCE & DISTRIBUTION OF TWO BLACK SEA CUCUMBER SPECIES IN POMBO ISLAND, CENTRAL MALUKU (INDONESIA) - Setyastuti, Ana (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2015)
The so called âblack sea cucumberâ are found in Indonesia as several species including HolothuriaÂ atra, H. leucospilota, H. coluber, H. excellens and H. turriscelsa. The local community of Wainure village near Pombo Island in central Maluku had reported that most sea cucumbers inhabiting the island are the black sea cucumbers or locally known as âteripang hitam.â They are occasionally consumed but not exploited excessively by the locals. The goals of this study are to identify the species of black sea cucumbers inhabiting Pombo Island and map their distribution to understand the microhabitats of black sea cucumber. Two field surveys conducted in March and April 2014 collected more than 550 individuals of black sea cucumbers that belong to two speciesÂ Holothuria (Halodeima) atra Jaeger, 1833, and Holothuria (Mertensiothuria) leucospilota Brandt, 1835. Furthermore, distribution maps of these two species show that they are found only along the SE to SW coast of the island. Such distribution may relate to the availability of marine vegetation, as well as boulders and stones that provide shelters to the organism. The distribution maps also show that H. atra has a wider distribution than H. leucospilota in Pombo Island. This may be due to the semi-cryptic habit of H. Leucospilotaâs (i.e. hiding its posterior body under rocks or crevices), making its distribution restricted to areas that provide ample shelters.